Lessons from aviation - the role of checklists in minimally invasive cardiac surgery. (January 2016) - Hussain, S; Adams, C; Cleland, A; Jones, PM; Walsh, G; Kiaii, B
We describe an adverse event during minimally invasive cardiac surgery that resulted in a multi-disciplinary review of intra-operative errors and the creation of a procedural checklist. This checklist aims to prevent errors of omission and communication failures that result in increased morbidity and mortality. We discuss the application of the aviation - led "threats and errors model" to medical practice and the role of checklists and other strategies aimed at reducing medical errors.